Effects of Radiation on Materials: 21st International Symposium 2004
DOI: 10.1520/stp11255s
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Pre-Irradiation Heat Treatments on Thermal Non-Equilibrium and Radiation-Induced Segregation Behavior in Model Austenitic Stainless Steel Alloys

Abstract: Abstract:The effect of pre-irradiation heat treatments on thermal non-equilibrium grain boundary segregation (TNES) and subsequent radiation-induced grain boundary segregation (RIS) is studied in a series of model austenitic stainless steels. The alloys used for this study are based on AISI 316 stainless steel and have the following nominal compositions: Fe-16Cr-13Ni-1.25Mn (base 316), Fe-16Cr-13Ni-1.25Mn-2.0Mo (316 + Mo) and Fe-16Cr-13Ni-1.25Mn-2.0Mo-0.07P (316 + Mo + P). Samples were heat treated at temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
2
6
0
Order By: Relevance
“…Jiao et al [24]mentions that displacement bends are complimentary nucleation positions on behalf of precipitates rich in [Ni]/[Si]. The increase of [Ni] and [Si] with depth, see Figure 8, agrees with our observations made by TEM [22], where the presence of dislocation loops was observed whose density concentration…”
Section: Analysis By X-ray Photoelectron Spectroscopysupporting
confidence: 89%
See 1 more Smart Citation
“…Jiao et al [24]mentions that displacement bends are complimentary nucleation positions on behalf of precipitates rich in [Ni]/[Si]. The increase of [Ni] and [Si] with depth, see Figure 8, agrees with our observations made by TEM [22], where the presence of dislocation loops was observed whose density concentration…”
Section: Analysis By X-ray Photoelectron Spectroscopysupporting
confidence: 89%
“…It should be noted that the density of the iron [Fe] is of 7.91 gcm À3 . This steel presented an austenitic structure with lattice parameter a 0 in bulk of 0.35896 nm [22]. The cleaning procedure for the samples is explained in the following lines: (i) a 15 min ultrasonic bath in a trichloroethylene ([C 2 HCl 3 ], 99.9 %, from Sigma-Aldrich Química, S.L.…”
Section: Methodsmentioning
confidence: 99%
“…One such APT reconstruction is shown in figure 1a, which shows the level of grain boundary enrichment of these elements. Grain boundary enrichment of Cr was also observed in literature with annealing [8]. No other features are observed by APT in this material.…”
Section: Annealed Samplessupporting
confidence: 86%
“…While the previous study shows the composition gradient that formed from the transient state has an important role in the steady-state microchemistry at defect sinks, Busby et al [17] found that the pre-existing Cr-enrichment at grain boundary due to thermal segregation also leads to the oscillatory behavior of segregation profiles during the subsequent irradiation. Similarly, Cole et al [18] found Cr, Mo and P in 316SS under different cooling rates had already enriched to various levels at grain boundary before the materials being exposed to irradiation environments. The higher the enriched levels lead to the more pronounced W-shape profile during the subsequent irradiation.…”
Section: Introductionmentioning
confidence: 76%